Phi Sigma Chi Fraternity members at Montgomery Hotel - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic group portrait. A group of men gather around a fraternity flag. The two men holding the flag have cigars in their mouths. The greek letters down the center of the flag translate as Phi Sigma Chi. On the bottom left corner the Greek translation is Epsilon Mu. A majority of the men are wearing ribbons. Some of the men are wearing class rings. Most of the men are dressed in formal attire. Behind the group and to the right of the photo is Majestic Electric Refrigerator store.